Influence of refractory on the color of VM7 metal free ceramics - Renato Fabricio de Andrade Waldemarin; Cari Maristela Pieper; Guilherme Briao Camacho (Wolters Kluwer Medknow Publications, 2015)
Introduction: The aim of this study was to evaluate the influence of metal oxides from investment dies on the color of metal-free VM7 ceramic. Materials and Methods: Forty circular patterns were made with an elastic gelatin duplicator. These were divided into four groups (n = 10) for pouring the investment: G1, Begoform (Bego); G2, Ducera Lay Superfit (DeguDent GmbH); G3, Duravest (Polidental), and G4, Refrax Magnum (CNG). Refractory dies were subjected to the degassing process for gas and metal oxide elimination, and the testing was done with the application of two layers of VM7 ceramic. These layers were sinterized in accordance with the manufacturer's recommendation and then glazed. For the control group, 10 additional VM7 ceramic discs were made without the use of any investment die. The ceramic's control color and the tested groups were analyzed with the aid of a portable colorimeter (Minolta CR-10) in the CIELab. The color change (ΔE) of the specimens from the tested groups was obtained, and the data were submitted to one-way ANOVA and post-hoc Tukey's test. Results: All tested groups had a color change from the control group. G1 (5,3) and G2 (5,3) were those that showed the greater color change and did not show statistical differences between themselves; G3 (3,3) and G4 (3,1) were those that showed the least color change from control group and did not show statistical differences between themselves. Conclusion: Once all investments present a perceptible color change from the control group, color selection should be done with a laboratory-produced color scale.